Earth’s Outgoing Longwave Radiation Variability Prior to M ≥6.0 Earthquakes in the Taiwan Area During 2009–2019 - Fu, Ching-Chou; Lee, Lou-Chuang; Ouzounov, Dimitar; Jan, Jyh-Cherng (Frontiers in Earth Science, 2020)
This paper proposes an analysis method, using the National Oceanic and Atmospheric Administration satellite data, to trace variations in outgoing longwave radiation (OLR) for finding the precursors of earthquakes. The significance of these observations is investigated using data sets of recent M ≥ 6.0 earthquakes around the Taiwan area from 2009 to 2019. We suggest that the precursory signal could be an EIndex anomaly (EA) in the form of substantial thermal releases distributed near the epicenter. The consecutive appearances of OLR EAs are observed as precursors two to fifteen days before significant earthquakes, and we refer to this as a pre-earthquake OLR EIndex anomaly (POEA). We interpret these thermal sources as possibly originating from electromagnetics together with gas emissions associated with pre-seismic processes. This study highlights the potential of OLR anomalous changes in earthquake precursor studies, at least in the Taiwan region.